De-constructing the Imaginary Child in Greek Cypriot Contemporary Young Adult Fiction Novels - Rosy-Triantafyllia Angelaki (Leaf Journal)
According to literary critics, contemporary Young Adult novels reflect the adolescents’ literary and psychological needs and focus on the de-naturalization of traditional identities and family patterns in order to deromanticize adolescence, as it can be a real identity crisis. Taking this into account, it is interesting to examine how male and female adolescents personalities’ are constructed in Young Adult fiction within dialogic negotiations with society and family, where death is experienced literally and metaphorically due to multiple forms of victimization. This paper focuses on Andri Antoniou’s polyphonic – and full of narrative complexities and dialogical resonances – fiction novels and examines how the Greek Cypriot Young Adult fiction author subverts the “adult’s desire for the child” and challenges the myth of innocence in young age with her realistic and often naturalistic writing, reminding critical theorists’ arguments that Young Adult fiction advocate psychoanalytical readings. Drawing on Young Adult fiction Literary Criticism, qualitative content analysis and the main principles of New Criticism, the way Antoniou represents male and female adolescents personalities to grow into maturity through death, depression, substance use and violence will be examined; additionally, the way the adolescent characters negotiate with themselves and others in order to balance their own power against their parents (or other authority figures in their lives) and their abusers will also be investigated.